2016
DOI: 10.5812/jjm.29694
|View full text |Cite
|
Sign up to set email alerts
|

Detection of 23SrRNA Mutations Strongly Related to Clarithromycin Resistance in Helicobacter pylori Strains Isolated From Patients in the North of Iran

Abstract: Background:Helicobacter pylori is curved Gram negative and microaerophilic bacilli that have infected half of the world’s population. It is recognized as the causative agent of duodenal ulcer, gastritis peptic ulcer, mucosa-associated lymphoid tissue (MALT) lymphoma and is associated with gastric adenocarcinoma. Resistance to clarithromycin is related to point mutations in 23SrRNA gene on nt 2143 and 2144, when A turns to G, and A2143G is the most important type. These mutations lead to reduced affinity of ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 19 publications
4
4
0
Order By: Relevance
“…A high relative frequency of resistance was seen in CAG patients; however, there was no significant relationship between various diseases and clarithromycin resistance status. These findings are in agreement with Eghbali et al [32].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…A high relative frequency of resistance was seen in CAG patients; however, there was no significant relationship between various diseases and clarithromycin resistance status. These findings are in agreement with Eghbali et al [32].…”
Section: Discussionsupporting
confidence: 94%
“…In this study, although the relative frequency of clarithromycin resistance was higher in females than males, the difference was not significant. This is consistent with the findings of others [12,32]. The consumption of new macrolides, which are commonly prescribed in the elderly, can lead to more mutations.…”
Section: Discussionsupporting
confidence: 93%
“…In general, in our study, the most frequent mutation responsible for resistance to clarithromycin was found in the rrl gene in the A2147G allele in accordance with other reports . Mutations responsible for fluoroquinolones resistance with highest frequency were found in the N87K allele on the gyr 87 gene and in the D91N allele on the gyr91 gene in accordance with other reports .…”
Section: Discussionsupporting
confidence: 92%
“…Subgroup analysis based on PCR methods Several PCR-based methods were applied in these 22 studies. Including PCR-RFLP, 34,35,37,[41][42][43][44][45][46] PCR-based sequencing, 40,47-52 fluorescent in situ hybridization (FISH), 36,50,52 scorpion PCR assay, 43,53 GenoType HelicoDR, 51 PCR-line probe assay, 24 LightCycler PCR, 54 denaturing HPLC (DHPLC) assay, 23 and primer-mismatch PCR. 46,55 The pooled sensitivity and specificity for any of these assays were greater than 0.95, except for GenoType HelicoDR, which had a sensitivity of 89.6%.…”
Section: Performance Of Genotypic Methods In Cultured Strainsmentioning
confidence: 99%